(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This research presents a comprehensive analysis of a reinforced concrete (RC) bridge using the MATLAB software for the assessment of structural response under static, dynamic, and thermal loads. The bridge model (length 50 m, width 20 m, height 8 m) is supported by three columns, with a reinforcement ratio of 2% and a foundation area of 25 m². Results: Maximum static deflection was 13 mm at mid distance; thermal stress was 50.4 MPa up 20°C gradient. Natural Frequency at 1 Hz (6.2832 Rad/S) with 5% Damping Ratio. The design satisfies the ACI 318-19 and Eurocode 2interaction, with this example proving MATLAB is suitable for structural optimization.